Developing a Framework to Facilitate â€œJoint Effortâ€ Initiatives in Malaysian Industrialized Building System (IBS) Projects - Salman Riazi Mehdi Riazi; Ismail Ishak; Mohd Nasrun Mohd Nawi (International Journal of Supply Chain Management, 2019)
Poor ability to meet growing housing demands are a major problem for Malaysia. Despite the initiatives to move towards the uptake of Industrialized Building System (IBS), it has been hampered by fragmentation issues, a typical picture of traditional mentalities. â€œJoint Effortâ€, initiatives have the potential to rescue the current predicament however, the industry hesitance has been a major hindering factor. This paper reports the progress to date of on-going research aimed at developing a validated framework to facilitate â€œJoint Effortâ€ uptake in Malaysian IBS projects. â€œJoint Effortâ€, being among the core component of Supply Chain Management (SCM), is a collaborative endeavor that has the potential to overcome fragmentations. It leans towards the creation of effective teamwork which benefits all parties at both short and long term. Encouraged by a few success cases, there is cautious optimism that it may as well benefit the Malaysian dilemma. This paper considers fragmentation as a major hindrance on IBS uptake, establishes the need to embrace â€œJoint Effortâ€ initiatives and then elucidates the needs and strategies towards coming out with the final research framework. A combination of quantitative and qualitative approaches will be used and the final outcome will be a framework that proposes beneficial tools to curb the critical barriers to â€œJoint Effortâ€ uptakes. It is expected that the framework would aid in improving IBS practices thus better able to meet the housing demands.